Italy : Technical Note on Insurance Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This Technical Note covers the insurance sector of Italy supervised by the Institution for the Supervision of Insurance in Italy. Notwithstanding the high level of compliance with the International Association of Insurance Supervisors principles, critical principles remain to be taken on. Twenty one principles are fully or largely observed; however, the remaining five principles that are partly observed are central to maintaining financial stability of the sector and preventing possible unexpected insolvencies. The anti-crisis measures introduced for the insurance sector have also helped the sector navigate through the recent sovereign debt volatility and created an effective early warning supervisory tool.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet